Food and feeding habits of Acetes japonicus in the coastal waters of Malacca, Peninsular Malaysia - Norsharida Md. Saad.
The food habits of the Acetes japonicus, in the coastal waters of Malacca, Peninsular Malaysia were investigated monthly by examining the stomach contents of 131 specimens collected from April 2007 to March 2007. Of the total stomachs examined, 11% were empty. Prey analyses of the stomach contents identified eight groups of food item: phytoplankton, zooplankton, algae, decapod appendages, plant matter, debris, unidentifiable species and sand and mud. Based on food items in the stomachs, A. japonicus can be categorized as omnivore. According to Simple Resultant Index (Rn), the most important food items for A. japonicus were plant matter (31.82%) which is in the first ranked. This followed by debris (20.06%), phytoplankton (18.45%), sand and mud (11.75%), parts of decapods (6.00%), unidentifiable species (5.86%) and algae (4.17%). Zooplankton (1.80%) seems to be the least prefered food items consumed by A. japonicus from coastal waters of Malacca since the item was in the last ranked of Simple Resultant Index.